Peningkatan Kompetensi Menulis Teks Cerita Sejarah dengan Metode Team Games Tournament (TGT) Siswa Kelas XII IPS 3 SMAN 3 Selong - Muttaqin, Zainul; Khalisatun, Khalisatun (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2019)
The implementation of team games tournamentâ€™s (TGT) type in increasing students competence in writing historical text story of Indonesian language with the aim to know the students competece in writing historical text story in XII IPS 3 class of SMAN 3 Selong. The researcher uses the action class research. The data collection is observation and test then use qualitative and quantitative descriftive analysis. The research is applied in two periods. The first period, there were nine students who got high value, seven students who got medium, and ten students who got low. So, in the first period only got 61,5%. It means that the researcher should do the next step. Meanwhile, in the second period, there were twenty students who got high value, four students who got medium, and two students who got low. So, the research in the second period by using cooperative learning team games tournamentâ€™s type in arranging travel text got the target that is 88,4%. The results indicated that TGT could develop the students competence in writing historical text story in Indonesia language lesson.      Key words: Kooperatif Learning; Team Games Tournament; dan Historical Text Story